Effect of Warm Compress on Neck Pain Scale Reduction in CKD Patients with Hypertension - Hajjan, Miftakhulidayanti; Kartikasari, Dian; Kusumarini, Eny (KIAN JOURNAL, 2025)
Introduction: Hypertension can result in kidney failure if not treated promptly and is frequently a chronic condition. Common symptoms include headaches, dizziness, and neck pain. Applying warm compresses to the neck may help alleviate pain for patients with hypertension. Objective: This study aims to evaluate the effectiveness of warm compresses in reducing pain levels among chronic kidney disease (CKD) patients with hypertension in Sulaiman Room 6 at Roemani Muhammadiyah Semarang Hospital. Methods: This research is a descriptive study with a case study approach method. The subject used was 1 person with the criteria of hypertensive patients with systolic blood pressure ≥ 140 mmHg and diastolic ≥ 90 mmHg, composmentis, pain scale 4-6, and no neck injuries. Results: The results indicated that the pain level in the neck before applying the warm compress was moderate, rated on a scale of 5. After using a warm compress for three sessions of 15 minutes each, the pain level decreased to a scale of 2, which is classified as mild. Conclusion: The application of warm compresses on the neck effectively reduces the head pain scale of hypertensive patients.